Tamil Media in Ten Years After War Period - Raguram, S. (Voice of Jaffna Publications, Jaffna, 2019)
Ten years ago, the Tamils experienced dawn filled with helplessness and all the expectations were shattered instantly. Since then people live in an environment filled with stress and search questions regarding coexistence and rights. Against this backdrop, it’s deliberating about freedom of community and the media freedom the people are entitled to. This research focuses on the roles and responsibilities of journalists and the changes that can be made through fulfilling those obligations. Tamil journalists maintain a close relationship and understanding with journalists and media institutions representing the majority community. This helps the Tamil journalists to come out of the crisis and stress they face. The journalists and media outlets were instrumental in bringing the current regime into power. This can be seen as an opportunity in terms of strategy to resolve the crisis faced by the Tamil community. These developments can be considered as tactical changes that occurred in the threat levels or ways of enforcing violence and they cannot be considered as flexibilities or changing of stances of government or security forces approaching the media.